Radiation and mass transfer effects on MHD free convection flow past a moving vertical cylinder in a porous medium - Suneetha, S.; Reddy, N. Bhaskar (Journal of Naval Architecture and Marine Engineering, 2011)
The interaction of free convection with thermal radiation of a viscous incompressible unsteady MHD flow past a moving vertical cylinder with heat and mass transfer in a porous medium is analyzed. The fluid is a gray, absorbing-emitting but non-scattering medium and the Rosseland approximation is used to describe the radiative heat flux in the energy equation. The governing equations are solved by using an implicit finite-difference scheme of Crank-Nicolson type. The effects of various physical parameters such as thermal Grashof number, mass Grashof number, magnetic parameter, radiation parameter and Schmidt number on the velocity, temperature, concentration, local as well as average skin-friction, Nusselt number and Sherwood number for various parameters are computed and represented graphically. It is found that at small values of radiation parameter , the velocity and temperature of the fluid increases sharply near the cylinder as the time increases. Also, an increase in the magnetic field leads to a decrease in the velocity and a rise in the temperature.As the permeability parameter increases,it is seen that the flow accelerates. This model finds applications in geophysics and engineering. DOI: 10.3329/jname.v7i1.2901